INTUITIONISTIC FUZZY LATTICE ORDERED M-GROUPS - Makandar, M.U. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
This paper contains some definitions and results in intuitionistic fuzzy lattice ordered M-groups, which are required in the sequel. Some properties of homomorphism and anti-homomorphism of intuitionistic L-fuzzy M-subgroups are also established. Keywords-fuzzy m subgroup, lattice ordered m-group, Anti L-fuzzy M-subgroup, intuitionistic fuzzy lattice ordered Â M-groups